A dual enzymatic amplified strategy for the detection of endonuclease V activity. Issue 19 (7th October 2015) - Wang, Wei; Peng, Feifei; Li, Wang; Huang, Yan; Nie, Zhou; Yao, Shouzhuo
<x xml:space="preserve">Abstract</x> A dual enzymatic amplified strategy for the detection of endonuclease V activity was developed based on in situ synthesis of fluorescent CuNPs.